Update on Prevention of Mother-to-Child HIV Transmission - Lynne M. Mofenson (Hindawi Limited, 2004)
The pediatric HIV epidemic in the US and other more developed countries changed dramatically after February 1994, when the results of PACTG 076 demonstrated that a triple regimen of ZDV reduced the risk of perinatal transmission by nearly 70%. Incorporation of ZDV prophylaxis into clinical practice, together with increased prenatal HIV counseling and testing, rapidly resulted in a significant decline in perinatal transmission and a concomitant decrease in the number of reported pediatric AIDS cases in the US. Transmission rates of 3-6% have been reported in various cohort studies with ZDV prophylaxis alone, and of 1-2% when ZDV is combined with elective Cesarean delivery or when women are treated with highly active antiretroviral regimens that reduce maternal viral load to unquantifiable levels. Additionally, several short antiretroviral regimens, including those that require administration only during the intrapartum and early postpartum periods, have been shown to decrease perinatal transmission. These regimens provide effective intervention even for HIV-infected pregnant women who have not received antiretroviral therapy and are identified late in pregnancy or for the first time at delivery through rapid HIV testing.